Settings in Trading Services International Economic Law - Peicheng Cheng (International Journal of Science and Society, 2019)
International trade, as one part of economic activity or business activities, in the last decade, has shown very rapid development, amid increasing business attention on global business activities. This phenomenon can be seen from the increased circulation of goods, services, capital and labor between countries, and the development of business activities through export-import relations, investment, service trade, licensing and franchising, intellectual property rights, and various other international types trading.